2013
DOI: 10.1186/1471-2482-13-s2-s55
|View full text |Cite
|
Sign up to set email alerts
|

Short-time prone posturing is well-tolerated and reduces the rate of unintentional retinal displacement in elderly patients operated on for retinal detachment

Abstract: PurposeTo evaluate the feasibility, efficacy and safety of strict prone posturing taken for 2 hours after operation in preventing the occurrence of unintentional retinal displacement in elderly patients operated on for retinal detachment (RD).MethodsTwenty patients aged 60 or more with diagnosis of macula-off RD were asked to keep a strict face-down posturing for 2 hours after vitrectomy and 20% sulfur hexafluoride tamponade. IOP was measured immediately before and after surgery and after the 2-hour posturing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
0
25
1
Order By: Relevance
“…While some of the variation may be due to surgical technique or any postoperative posturing advised, it is also possible that differences in detection rates result from different imaging systems. Studies that used FCs found an incidence of between 60 and 72% [1,2,4,5], whereas studies using a cSLO system found an incidence of 14-41% [3,7,8]. Differences between these 2 imaging modalities in detecting macula pathology have previously been reported [9,10], as has a difference in the gradability of the images due to signal to noise ratio [10].…”
Section: Post-rd Retinal Shift Faf Comparison 281mentioning
confidence: 99%
“…While some of the variation may be due to surgical technique or any postoperative posturing advised, it is also possible that differences in detection rates result from different imaging systems. Studies that used FCs found an incidence of between 60 and 72% [1,2,4,5], whereas studies using a cSLO system found an incidence of 14-41% [3,7,8]. Differences between these 2 imaging modalities in detecting macula pathology have previously been reported [9,10], as has a difference in the gradability of the images due to signal to noise ratio [10].…”
Section: Post-rd Retinal Shift Faf Comparison 281mentioning
confidence: 99%
“…Unintentional macula displacement or "macula shift" can complicate otherwise anatomically successful repair of macula-involved or macula-uninvolved retinal detachments (RD) [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Vitrectomy with standard subtotal volume isovolumetric gas tamponade has been reported to be associated with fundus autofluorescent (FAF) shift rates between 23 and 72% [1][2][3][4][5][6][7][8][9]. Most series contain patients with both maculainvolved and macula-uninvolved RD.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a supine or prone postoperative positioning has been evaluated, with or without the use of PFCO, to detect whether these differences in the surgical procedure can cause any difference in the occurrence of retinal folds. The results showed that the presence of retinal folds was similar in all groups, so neither the possible use of PFCO nor the different postoperative positioning seems to play a role (Dell'Omo et al 2013). The immediate pressure on the retina caused by the PFCO use does not seem to affect the occurrence of the retinal folds, also because the PFCO usually is removed within minutes during surgery.…”
Section: Discussionmentioning
confidence: 89%